Implementation of Edupreneurship in Students of the Equivalency Education of the Salafiyah Sirojul Munir Pati Islamic Boarding School in the 2024/2025 Academic Year - Edi Karisma; Islah Gusmian (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
This study aims to (1) determine how edupreneurship is implemented in developing students' life skills, including technical skills, work character, and practical experience. (2) describe and understand the forms of edupreneurship applied to students of the Equivalency Education School of Salafiyah Sirojul Munir Pati. (3) determine how edupreneurship is managed, including planning, mentoring, implementation, and program evaluation within the Islamic boarding school environment. The research method used was descriptive qualitative, conducted on October 6, 2025, with data collection through interviews, observation, and documentation. The research subjects consisted of Islamic boarding school administrators, business unit managers, and informants consisting of religious teachers (ustadz), and students of equivalent education. Data collection techniques used observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Data validity was maintained through source triangulation and techniques developed by Miles and Huberman. The research results indicate that(1) the implementation of edupreneurship in the equivalent education at the Salafiyah Sirojul Munir Islamic Boarding School is carried out through practice-based learning, where students are directly involved in the production and marketing processes. This activity develops students' life skills, both technical and non-technical, such as discipline, responsibility, cooperation, creativity, communication, and problem-solving.(1)The edupreneurship program focuses on two main business units: avocado and durian nurseries, and honey cultivation and marketing, which not only have economic value but also serve as a means of entrepreneurship training.(1) The management system is structured through task allocation, on-duty duties, activity reports, and regular evaluations with intensive mentoring. Overall, this program has been effective, fostering independence and an entrepreneurial mindset in students, and integrating religious education with economic empowerment in an adaptive and sustainable manner.